An Analysis Of Service Quality at The Samsat Office of Nabire Regency, Papua Province, Indonesia. - Wijayatiningsih, Hana Prihatini; Pakasi, Usman; Sardjijo, Sardjijo (PINISI Discretion Review, 2021)
This research aims to examine the quality of the services of the Samsat Office (Vehicle Document Registration Center) of Nabire Regency, Papua Province, the obstacles encountered in the service provision, and the efforts to tackle such obstacles. A mix of qualitative and quantitative methods was employed in conjunction to a descriptive approach. Research data were collected through interviews, questionnaire distribution, observation, and documentation, and they were analyzed through data reduction, data presentation and conclusion drawing, and SERVQUAL analysis. The informants recruited in this research were taxpayers as the customers of the services as well as the officials and officers of the Samsat Office of Nabire as the providers of the services. The analysis of the service quality rendered by the Samsat Office of Nabire Regency, Papua Province, that involved measurement of service dimensions of tangibles, reliability, responsibility, assurance, and empathy revealed that the services provided were not of excellent quality. The results of the SERVQUAL analysis also showed that all the indicators used yielded negative gap scores. The obstacles faced lied in insufficient number of personnel and personnel’s poor discipline, insufficient information on the service procedures and payment details, improper layout, absence of service standards, unsupportive facilities and infrastructures, and imposition of roadside parking retribution. Some efforts to tackle such obstacles may take the form of a plan of alteration to the service room and counter layouts according to the applicable SOP, improvement of the quantity and quality of human resources, improvement of information dissemination through socializations and publications, innovation-making to facilitate payments, and improvement of service provision facilities, infrastructures, and equipment.